(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
In 1985, the Minas Gerais Puppet Theater Association (ATEBEMG) was created, responsible for promoting, over the years, important dialogues and projects of its members, among which we can affirm the fundamental presence of the puppeteer Conceição Rosière who contributes, always, for the longevity and vigor of the Association. As a puppeteer, teacher, researcher and member of ATEBEMG, and considering the global situation caused by Covid-19 and the “triggering” and latent theme proposed by Móin-Móin Magazine - The performance of women in the Animation Theater -, I felt instigated to register part of the path taken by Conceição Rosière and, to interview her in the virtual modality and, thus, to share with different readers the female voice translated in the force of a collective.